PRODUTIVIDADE DA SOJA COM O USO DE FERTILIZANTE ORGANOMINERAL EM SOLOS COM DIFERENTES TEXTURAS - BARBOSA, Bruno Rafael Simbre; GAIOLA, Lucas Henrique de Oliveira; SANTOS, Benjamin Abel dos; MACHADO, Cauã Melo; BONFIM, Willian Gabriel Alves; ZOZ, Tiago (ANAIS DO ENIC, 2025)
-